COMMUNITY EMPOWERMENT IN CONTROL OF NON-COMMUNICABLE DISEASES THROUGH EDUCATION AND CARD MONITORING AT POSBINDU - Utami, Ressa Andriyani; Widagdo, Wahyu; Chairani, Reni; Solihah, Ii; Hasnani, Fenti (LPPM Univ. Ibn Khaldun Bogor, 2025)
Non-Communicable Diseases (NCDs) such as hypertension, diabetes mellitus, obesity, and heart disease are the leading causes of death in Indonesia. Low health literacy and limited community participation in the Posbindu NCD program hinder prevention efforts. This community service activity was conducted in RW 04 Kebagusan, South Jakarta, aiming to improve residents’ knowledge and skills in controlling NCD risk factors through health education and self-monitoring training. The program included interactive health education, hands-on workshops on blood pressure and Body Mass Index measurement, and distribution of self-monitoring cards. The pretest average score of 50.67 increased to 81.33 in the posttest, with a significant rise in the “good” and “excellent” knowledge categories. The program effectively enhanced health literacy and community engagement in NCD prevention. In conclusion, participatory community-based education successfully improved awareness, self-care skills, and the community’s sense of responsibility toward sustainable health maintenance.